The Oxford handbook of the Ethiopian economy - Fantu Cheru, 1949-; Cramer, Christopher (Professor of political economy); Oqubay, Arkebe (Oxford handbooks online., 2019)
From a war-torn and famine-plagued country at the beginning of the 1990s, Ethiopia is today emerging as one of the fastest-growing economies in Africa. This Oxford Handbook focuses on structural transformation to understand Ethiopia's unique model of development.